Stock Price Valuation in Making Investment Decisions (Study on Stocks Listed on The Indonesian Stock Exchange Jakarta Islamic Index 70 Period 2020 – 2022) - Nuraini, Tika Maulina; Martini, Tina (IAIN Kudus, 2023)
This study aims to examine the difference in stock valuation using the DDM and DCF methods for investment decision making in companies listed on the JII 70 for the period 2020 - 2022. This research is a type of descriptive research with a quantitative approach that originates from the annual reports of companies listed on JII 70 for the period 2020 - 2022 The sampling technique used purposive sampling with several predetermined criteria, in order to obtain 24 samples of companies with a period of 3 years to 72 samples. The data analysis technique uses the Dividend Discount Model and Discounted Cash Flow methods and then conducts a t-test. The results of this study indicate that if the share price is calculated using the Dividend Discount Model, the majority are undervalued. Meanwhile, the majority of stock prices calculated using the Discounted Cash Flow method are in overvalued condition. There is no difference in the Dividend Discount Model and Discouted Cash Flow methods, so the investors should not hesitate to choose between the two models.